Kajian Pengetahuan Ibu Tentang Autis dan Gizi Anak Autisdi Sekolah Luar Biasa (SLB) Negeri Nunumeu-Soe - Inri L. A. Sae; Afrona E. L. Takaeb; Helga J. N. Ndun (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Autism is a variant of autism spectrum disorder characterized by social communication difficulties and language barriers, narrow interests and rigid and repetitive behavior. This research aims to examine mothers' knowledge about autism and nutrition for autistic children at Nunumeu-Soe State Special School. This research is a qualitative research. Data collection was carried out using in-depth interview techniques with six informants who have autistic children at Nunumeu-Soe State Special School. The results of the research found that not all informants knew the symptoms of children with autism, so it was discovered that when children were 3-5 years old, the symptoms of autism that were often noticed were difficulty speaking and hyperactivity. Not all informants gave breast milk until the child was two years old due to work factors and replaced it with formula milk. All informants did not know the type of autistic behavior that influences children's consumption patterns, but the informants already knew the levels of autism. Mother's knowledge about nutrition for autistic children regarding types of food that adapt to the child's wishes containing gluten and casein. Food taboos in children are well known, but often escape the mother's attention due to permissive parenting, which causes serious symptoms in children. Barriers to health services and a lack of health workers in TTS district resulted in a lack of informant knowledge. Schools need to consult with local health services to educate parents about the nutrition of autistic children regarding the type of behavior and dietary restrictions of autistic children.